Heterosis for Biomass and Grain Yield Facilitates Breeding of Productive Dual‐Purpose Winter Barley Hybrids. Issue 5 (30th June 2017) - Bernhard, Timm; Friedt, Wolfgang; Voss‐Fels, Kai P.; Frisch, Matthias; Snowdon, Rod J.; Wittkop, Benjamin
Abstract : Winter barley ( Hordeum vulgare L.) can be a valuable supplement as whole plant silage for bioenergy production due to positive effects of plant cover over winter and the possibility of growing a subsequent second crop after barley. However, to be competitive with other bioenergy crops, barley dry matter yield (DMY) needs to be enhanced. Therefore, we tested a factorial of 96 barley experimental hybrids together with their parental lines for DMY, grain yield (GY), and yield‐associated traits in a multi‐environmental field plot trial with a practical focus. The average best‐parent heterosis (BPH) of GY was 7.7%, whereas average BPH of DMY was 9.1%. The higher GY of hybrids was mainly caused by the higher kernel number per ear. The variance of specific combining ability (SCA) was higher than that of general combining ability (GCA), revealing prevalence of non‐additive effects on barley DMY. Additionally, SCA values highly correlated with those of DMY and GY ( r = 0.752 and r = 0.839, respectively), as well as with values of mid‐parent heterosis (MPH; r = 0.768 [DMY], r = 0.877 [GY]) and BPH ( r = 0.695 [DMY], r = 0.768 [GY]). There was a correlation between the parental genetic distance and hybrid DMY, whereas no correlations were found between the parental per se and hybrid DMY and GY values. These results suggest that future hybrid breeding should be run in a separate program with a main focus on the establishment of heterotic pools and an increase in genetic diversity.